Efforts to Improve Religious Attitudes Through Habituation of Dhuha Prayers at Mts Nu Tirto Pekalongan - Anshory, Muhammad Isa; Nasarruddin, Razie Bin; Achmad, Dliya'uddin (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
The world of education has many goals, especially goals in the process of inculcating noble character in students. Noble morals can be achieved through a religious path, including the habit of praying dhuha. This study aims to determine 1) the effectiveness of the habituation of Duha prayer in increasing religious values, 2) Strategies in instilling religious values through the habit of Duha prayer. This study uses a qualitative approach with a descriptive method, namely in explaining the circumstances of the problem to be studied by using non-number terms. Data collection techniques in this study used the observation method to observe the process of efforts to increase the value of religiosity in students through dhuha prayers, interviews to receive data in the form of religious activities and strategies used in instilling religious values in students, and documentation to obtain data in the form of vision and mission , infrastructure, human resources. The data analysis techniques in this study were through data reduction, data modeling, and drawing conclusion/verification data. Sources of data obtained came from school principals, students, teachers, and PAI instructors at MTs Nu Tirto Pekalongan. The results of this study share that; 1) religious values that are instilled through the habit of praying dhuha at MTs NU Tirto Pekalongan mean worship values, anda moral values. 2) strategies in instilling religious values through the habituation of Duha prayer at MTs Nu Tirto Pekalongan namely reward and Punishment, exemplary, habituation, invitation (persuasive), rules or norms, and creating a religious atmosphere at school. The conclusion of this study is the character of religiosity through the habit of praying dhuha at MTs Nu Tirto Pekalongan by using various strategies in its development which are very clearly explained and synchronized to increase the religious character of students.